A statistical analysis of the effects of pressure, temperature and salinity on contact angles in CO2–brine–quartz systems. (November 2015) - Palamara, D.R.; Neeman, T.; Golab, A.N.; Sheppard, A.
Highlights: Contact-angle measurements are inconsistent between studies. Contact angles increase as pressure increases for subcritical CO2 conditions. Contact angles increase consistently with temperature and salinity. Abstract: An integrative data analysis was performed using previously published contact-angle data for CO2 –brine–quartz systems. Linear mixed-effects models were used to perform exploratory analyses of the influence of pressure, temperature and salinity on contact angles for subcritical and supercritical CO2 conditions. The results confirm that there is a large disparity in the magnitude and behaviour of contact angles between studies; accommodating this disparity through the use of a random effect suggests that changes in pressure are important mostly in the subcritical CO2 pressure range. Brine concentration and temperature are both statistically and practically relevant to the wettability of quartz in CO2 –brine systems across both pressure regimes.